Using Identification Codes in the Two-Party Privacy-Preserving Record Linkage (PPRL) - Yanling Chen (Journal of Universal Computer Science)
In this paper, we show the problem of two-party privacy-preserving record linkage (PPRL) can be seen as an identification problem in Information Theory. We propose to apply the identification codes that are designed for identification via channels to the problem of PPRL, due to their advantage in the performance analysis, especially on a quantitative evaluation of the privacy. Note that for the PPRL, linkage quality is typically evaluated experimentally, whilst for privacy, there are so far no commonly accepted privacy measures available that allow an objective evaluation. Our approach of identification code provides an objective evaluation on both linkage quality and privacy based on parameters of employed identification codes.